Reading Interventions for Middle and Secondary Students With Emotional and Behavioral Disorders: A Quantitative Review of Single-Case Studies. (January 2015) - Burke, Mack D.; Boon, Richard T.; Hatton, Heather; Bowman-Perrott, Lisa
Many students with emotional and behavioral disorders (EBD) experience learning problems in reading at the middle and secondary school levels. Yet, the academic performance of students with EBD is often overlooked in the research literature. The purpose of this article was to provide a quantitative synthesis of the published, peer-reviewed, single-case research literature on reading interventions for students with or at-risk for EBD. An omnibus nonoverlap effect size of .59 with a 95% confidence interval (CI) = [.54, .64] was found consisting of 219 phase contrasts and 44 participants across the 11 studies included in the review. The findings are discussed in the context of improving the academic and behavioral outcomes of middle and secondary students with EBD.